PERAN GURU DALAM MEMOTIVASI BELAJAR SISWA KELAS X PADA PEMBELAJARAN SOSIOLOGI DI SMAN 7 KABUPATEN TANGERANG - Audrey Rahmadanty; Septi Kuntari; Subhan Widiansyah (STKIP Subang, 2026)
Teachers play a crucial role in improving the quality of learning, particularly in motivating students to learn. This study aims to describe the role of teachers in motivating 10th-grade students in sociology classes at State High School 7, Tangerang Regency. This study was motivated by the low level of student enthusiasm in sociology classes, indicating the need to optimize the role of teachers in motivating student learning. This study employs a qualitative approach using a descriptive method, with data collection techniques including observation, interviews, and documentation, as well as data analysis conducted through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the role of teachers in motivating 10th-grade students’ learning is carried out through the provision of stimuli in the form of apersepsi, the use of engaging teaching methods by sociology teachers, communicative interaction, and the provision of verbal motivation. However, there are several obstacles faced by teachers, such as a lack of school facilities for the learning process and students who still require motivation to participate in sociology lessons. To address these issues, teachers strive to create a pleasant learning atmosphere and build closer interactions with students so that the learning motivation provided by teachers can be conveyed optimally.